2011
DOI: 10.1039/c0cc04862c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bispyrrolidine derivatives of H2@C60: differentiation of isomers using 1H NMR spectroscopy of endohedral H2

Abstract: Bisadduct isomers of a H(2)@C(60) derivative with nitroxide addends have been synthesized, isolated and characterized. The (1)H NMRs of endohedral H(2) of the major isomers show well-separated chemical shifts, which could be useful for structural assignment and identification of the purity of the C(60) bisadduct isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…The chemical shifts of the various isomers are distributed over ca. 2 ppm in a region about 2 ppm upfield from endo-H 2 O in the parent open fullerene, which is similar in extent and position to what was observed with our previously reported H 2 @C 60 nitroxide bisadducts and the NMR of endo 3 He in analogous bisadducts. However, because of the broadening effect from the attached nitroxide radical, some of the individual signals overlap and distinct isomers cannot be detected.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The chemical shifts of the various isomers are distributed over ca. 2 ppm in a region about 2 ppm upfield from endo-H 2 O in the parent open fullerene, which is similar in extent and position to what was observed with our previously reported H 2 @C 60 nitroxide bisadducts and the NMR of endo 3 He in analogous bisadducts. However, because of the broadening effect from the attached nitroxide radical, some of the individual signals overlap and distinct isomers cannot be detected.…”
supporting
confidence: 90%
“…By analogy with the 3 He measurements, we recently reported that bisadduct isomers of H 2 @C 60 derivatives can be differentiated by 1 H NMR spectroscopy of the endo-H 2 . The high sensitivity and short T 1 of 1 H NMR spectroscopy make this a very promising method in identifying H 2 @C 60 derivative isomers.…”
mentioning
confidence: 90%
“…[18,19] Moreover, similar derivatives, in which a nitroxide radical is connected to the endofullerene by a folded 3 10 -helical peptide, [20] and also bisadduct isomers of a H 2 @C 60 derivative modified with nitroxide appendages have also been reported. [21] In addition, the stereoselective synthesis of H 2 @C 60 , was first described by Martín and co-workers, reacting chiral ligands and metal salts through a 1,3-dipolar cycloaddition reaction of azomethine ylides. [22] Thus, an interesting finding regarding the encapsulation of a hydrogen molecule is that the process itself does not affect the reactivity or the stereoselectivity, as the observed results are similar to those of the hollow fullerene C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a small library of H 2 @C 60 derivatives covalently linked to a nitroxide radical have been prepared using either Prato or Bingel‐Hirsh methodologies [18,19] . Moreover, similar derivatives, in which a nitroxide radical is connected to the endofullerene by a folded 3 10 ‐helical peptide, [20] and also bisadduct isomers of a H 2 @C 60 derivative modified with nitroxide appendages have also been reported [21] …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The regiochemistry of the applicable reactions favors addition across [6,6] over [6,5] carbon-carbon bonds found on SWCNT caps and spherical fullerenes; calculations have shown that adducts to the [6,6] carbons are more thermodynamically stable, driven in part by the bond's more conducive π-orbital and alkene-like character. 24,25 Identical reaction mechanisms and products on C60 buckminsterfullerene (or "buckyballs"), a discrete and homogeneous allotrope of carbon, served as a platform in this work, to aid in the structural elucidation of SWCNT adducts that are resistant to standard spectroscopy methods.…”
Section: Introductionmentioning
confidence: 99%